Mammalian Bcnt/Cfdp1, a potential epigenetic factor characterized by an acidic stretch in the disordered N-terminal and Ser250 phosphorylation in the conserved C-terminal regions. Issue 4 (14th July 2015) - Iwashita, Shintaro; Suzuki, Takehiro; Yasuda, Takeshi; Nakashima, Kentaro; Sakamoto, Taiichi; Kohno, Toshiyuki; Takahashi, Ichiro; Kobayashi, Takayasu; Ohno-Iwashita, Yoshiko; Imajoh-Ohmi, Shinobu; Song, Si-Young; Dohmae, Naoshi
Abstract : We characterized the mammalian Bcnt/Cfdp1 (Bucentaur/craniofacial developmental protein 1) protein, a potential epigenetic factor, by showing that an acidic stretch in the N-terminal region and Ser 250 phosphorylation in the C-terminal region are critical for its anomalous SDS/PAGE mobility. Abstract : The BCNT (Bucentaur) superfamily is classified by an uncharacteristic conserved sequence of ∼80 amino acids (aa) at the C-terminus, BCNT-C (the conserved C-terminal region of Bcnt/Cfdp1). Whereas the yeast Swc5 and Drosophila Yeti homologues play crucial roles in chromatin remodelling organization, mammalian Bcnt/Cfdp1 (craniofacial developmental protein 1) remains poorly understood. The protein, which lacks cysteine, is largely disordered and comprises an acidic N-terminal region, a lysine/glutamic acid/proline-rich 40 aa sequence and BCNT-C. It shows complex mobility on SDS/PAGE at ∼50 kDa, whereas its calculated molecular mass is ∼33 kDa. To characterize this mobility discrepancy and the effects of post-translational modifications (PTMs), we expressed various deleted His–Bcnt in E. coli and HEK cells and found that an acidic stretch in the N-terminal region is a main cause of the gel shift. Exogenous BCNT/CFDP1 constitutively expressed in HEK clones appears as a doublet at 49 and 47 kDa, slower than the protein expressed in Escherichia coli but faster than the endogenous protein on SDS/PAGE. Among seven in vivo phosphorylation sites, Ser 250, which resides in a region between disordered and ordered regions in BCNT-C, is heavily phosphorylated and detected predominantly in the 49 kDa band. Together with experiments involving treatment with phosphatases and Ser 250 substitutions, the results indicate that the complex behaviour of Bcnt/Cfdp1 on SDS/PAGE is caused mainly by an acidic stretch in the N-terminal region and Ser 250 phosphorylation in BCNT-C. Furthermore, Bcnt/Cfdp1 is acetylated in vitro by CREB-binding protein (CBP) and four lysine residues including Lys 268 in BCNT-C are also acetylated in vivo, revealing a protein regulated at multiple levels.